An integrated approach to analyzing (adaptive) co-management using the 'Politicized' IAD Framework - Whaley, Luke; Weatherhead, E. K. (The Resilience Alliance, 2014)
Scholars of co-management are faced with a difficult methodological challenge. As co-management has evolved and diversified it has increasingly merged with the field of adaptive management and related concepts that derive from resilience thinking and complex adaptive systems theory. In addition to earlier considerations of power sharing, institution building, and trust, the adaptive turn in co-management has brought attention to the process of social learning and a focus on concepts such as scale, self-organization, and system trajectory. At the same time, a number of scholars are calling for a more integrated approach to studying (adaptive) co-management that is able to situate these normative concepts within a critical understanding of how context and power fundamentally influences the behavior of a system. In this paper we propose that Clement’s (2010) ‘politicized’ version of the Institutional Analysis and Development (IAD) Framework, originally developed by Elinor Ostrom and her colleagues, is well suited to addressing this challenge. The Framework provides breadth, clarity and structure by drawing the analyst’s attention to the range of variables and questions to be considered when attempting a study of co-management, the various components of the situation and the ways in which they interact, and the criteria the analyst may wish to adopt in evaluating the outcomes of the process. Alongside its ability to address contextual factors and power dynamics, the socio-economic and institutional dimension of the politicized IAD Framework means that it can be used to conduct analyses that result in sound policy recommendations.
Keywords: comanagement; adaptive comanagement; IAD Framework; politicized IAD Framework; methodology; institutions; power; discourse; resilience; water